ANALISIS DAN PERANCANGAN SISTEM INFORMASI UNTUK PELAYANAN ADMINISTRASI WARGA KELURAHAN MALAKA SARI BERBASIS WEB - Angin, Marselinus Arapenta Perangin; Susilo, Joko (Institut Bisnis dan Informatika Kwik Kian Gie, 2022)
The Malaka Sari Village Office is a government agency that provides services to the community, such as making population documents. Every Monday to Friday, kelurahan employees provide services for making citizen documents, but this is still done manually, so the services provided are less than optimal and filing takes quite a long time. This study aims to make it easier for village employees to provide maximum service, as well as to make it easier for the community to submit documents personal identity. In conducting research, the authors use several supporting theories, namely Information Systems, Waterfall, PHP (HyperText Preprocessor), and others. In conducting research, the authors analyze the system that is currently running on Malaka Sari Village, and using data collection methods, namely conducting interviews, direct observation, literature study, and collecting documentation in the form of photos, videos and others, making it easier for writers to design information systems based on citizen data processing Website for the Malaka Sari Village. The design of the information system that is made, consists of system architecture design, Use Case Diagrams, Activity Diagrams, ERD (Entity Relationship Diagram), Class Diagrams, system design plans and menu structures, and using PHP (HyperText Preprocessor), and databases MySQL. The results of this study indicate that the design of a web-based citizen administrative service information system makes it easy for people who want to submit letters or documents that are self-identity in nature, and village employees in providing services to residents of the Malaka Sari Village, as well as helping maximize community services at the village office . Keywords: Information Systems Analysis and Design, PHP (HyperText Preprocessor), MySQL, Web-Based Information Systems, Administrative Services.